TEST OF ANTIBACTERY ACTIVITIES IN VIVO NON-POLAR FRACTIONS EXTRACT ETHANOL REST OF RAIN (Ruta angustifolia [L.] Press) ON MEMBER WHICH INFECTED Staphylococcus aureus AND Streptococcus mutans - Frida Rosenova; Haryoto Haryoto; Andi Suhendi (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2014)
Antibacterial activity in vivo study of ethanol extract nonpolar fraction of inggu stem (Ruta angustifolia [L.] Pers) was conducted on Staphylococcus aureus and Streptococcus mutans. It had a purpose to determine the effect of non polar fraction of ethanol extract of inggu stem on animals that had been infected by bacteria Staphylococcus aureus and Streptococcus mutans. Inggu stem powder was macerated with ethanol 96% and fractionated by vacuum liquid chromatography using hexane : chloroform 6:4, 5:5, 4:6, 3:7. Inggu stem was tested with in vivo antibacterial activity on mice with various doses of 0.3, 1.2 and 2.14 g/kg. Intraperitoneal fluid of mice had been treated was cultured on agar media and colonies of formed bacteria were counted. Antibacterial activity on Staphylococcus aureus bacteria has an average percentage of inhibition for colony are respectively 73, 81 and 97 %., whereas that of the Streptococcus mutans bacteria are 41,81 and 97% respectively. Identification of thin layer chromatography fraction in nonpolar compounds of ethanol extract of inggu stem is indicated by flavonoids, terpenoids, and alkaloids.